2020
DOI: 10.5539/jas.v12n11p307
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnopharmacological Literature: An Analysis of the Scientific Landscape in the Cerrado in Central-Western Brazil

Abstract: Research on pharmacology and phytochemistry originating from medicinal plants has resulted in various publications highlighting the Cerrado in central-western Brazil, which has a remarkable diversity of plant species. The reserve area selected was the Cerrado stricto sensu settlement “17 April”, Mato Grosso do Sul (MS), Brazil. However, no ethnopharmacological review focusing on the plants present in the reserve area exists, even though the consumption of medicinal plants is a widespread pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In this context, the Cerrado is the second largest biome in terms of extension, located in the center of the country and formed by pastures, savannas and forests [8]. The study by Santos et al [9] carried out a survey of plants in a reserved area and identified 89 different species of medicinal plants from 39 different families. In addition, the authors point out that only three of these species are included in the National List of Medicinal Plants of Interest in the Single Health System of Brazil (SUS).…”
mentioning
confidence: 99%
“…In this context, the Cerrado is the second largest biome in terms of extension, located in the center of the country and formed by pastures, savannas and forests [8]. The study by Santos et al [9] carried out a survey of plants in a reserved area and identified 89 different species of medicinal plants from 39 different families. In addition, the authors point out that only three of these species are included in the National List of Medicinal Plants of Interest in the Single Health System of Brazil (SUS).…”
mentioning
confidence: 99%